-5(1-5x)+5(-8x-2)=-4x-8x+3

Simple and best practice solution for -5(1-5x)+5(-8x-2)=-4x-8x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(1-5x)+5(-8x-2)=-4x-8x+3 equation:


Simplifying
-5(1 + -5x) + 5(-8x + -2) = -4x + -8x + 3
(1 * -5 + -5x * -5) + 5(-8x + -2) = -4x + -8x + 3
(-5 + 25x) + 5(-8x + -2) = -4x + -8x + 3

Reorder the terms:
-5 + 25x + 5(-2 + -8x) = -4x + -8x + 3
-5 + 25x + (-2 * 5 + -8x * 5) = -4x + -8x + 3
-5 + 25x + (-10 + -40x) = -4x + -8x + 3

Reorder the terms:
-5 + -10 + 25x + -40x = -4x + -8x + 3

Combine like terms: -5 + -10 = -15
-15 + 25x + -40x = -4x + -8x + 3

Combine like terms: 25x + -40x = -15x
-15 + -15x = -4x + -8x + 3

Reorder the terms:
-15 + -15x = 3 + -4x + -8x

Combine like terms: -4x + -8x = -12x
-15 + -15x = 3 + -12x

Solving
-15 + -15x = 3 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-15 + -15x + 12x = 3 + -12x + 12x

Combine like terms: -15x + 12x = -3x
-15 + -3x = 3 + -12x + 12x

Combine like terms: -12x + 12x = 0
-15 + -3x = 3 + 0
-15 + -3x = 3

Add '15' to each side of the equation.
-15 + 15 + -3x = 3 + 15

Combine like terms: -15 + 15 = 0
0 + -3x = 3 + 15
-3x = 3 + 15

Combine like terms: 3 + 15 = 18
-3x = 18

Divide each side by '-3'.
x = -6

Simplifying
x = -6

See similar equations:

| 13y+5=5y-5 | | 2(x-4)=4(x-2) | | X-(-2)=6 | | 5(x+3)=3(2x-1) | | 1a+2=(-9) | | -4x-5[-x+10]=-43 | | 6x-8(x+3)=-14 | | 8x+7x-6x=18 | | i=400*0.0013*2 | | -6x+4[-2x+8]=130 | | x^2+39x+47=0 | | -2+8=5-(10p+4) | | i=400*0.13*2 | | 2x+6[-5x-15]=190 | | 4-3x+8=5x-4 | | 70x^2-53x+9=0 | | 2(x+4)=x-7 | | 26x-14=3 | | -10+3m=2(4m+-5) | | X+50=210 | | 7x+6[-x-17]=-109 | | x+x+(x-45)+(x-45)+(x-45)=540 | | x=28.75+0.25y | | 2(x-1)+x=4+5 | | x=320+.2x | | 4x-y+65=180 | | 4(x+4)=x-7 | | 3x-7[2x+6]=90 | | 3x-1.8=1-x | | 6.9-3v=2.1 | | 2x+2y=65 | | -17(y+3)+6(4y-3)=6(y-5)+9 |

Equations solver categories